STRATEGY MANAGEMENT OF THE NATIONAL NARCOTICS AGENCY IN EAST JAVA PROVINCE IN EFFORTS TO PREVENT DRUGS ABUSE IN EAST JAVA - Adhima, Naila Fauza; Oktariyanda, Trenda Aktiva (Universitas Negeri Surabaya, 2023)
East Java Province is one of the provinces in Indonesia with a high rate of drug abuse cases based on the results of the 3rd Quarter 2022 Infographic. Efforts to prevent drug abuse cases in East Java need to be carried out to minimize the impact that occurs. These prevention efforts can be carried out by BNN East Java Province through appropriate strategic management so as to reduce the wrong use of drugs. The purpose of this study is to conduct further analysis regarding strategic management carried out by BNN East Java Province. This research is included in the type of descriptive qualitative research with data collection methods through interviews, observation, documentation, and literature review. The focus of this study uses the theory of J. David Hunger and Thomas L. Wheelen which includes environmental observation, strategy formulation, strategy implementation and evaluation and control using snowball sampling. While the data analysis technique is carried out through four stages, namely collecting related data, reducing the data obtained, presenting the data after being processed and drawing conclusions to find out the expected results. The results showed that the BNN of East Java Province conducted environmental observations by identifying internal factors and external factors of the organization, the formulation of strategies was carried out to determine the vision, mission, strategy and policies of the organization, then at the strategy implementation stage the BNN of East Java Province carried out four programs which included advocacy programs , alternative empowerment programs, community empowerment programs as well as information and education management programs that are well implemented and have a positive impact on efforts to prevent drug abuse by conducting an evaluation at the last stage to find out the various obstacles and obstacles faced. Provinsi Jawa Timur menjadi salah satu provinsi di Indonesia dengan tingkat kasus penyalahgunaan narkoba yang tinggi berdasarkan hasil Infografis Triwulan III Tahun 2022. Upaya pencegahan kasus penyalahgunaan narkoba di Jawa Timur perlu dilakukan guna meminimalisir dampak yang terjadi. Upaya pencegahan tersebut dapat dilakukan oleh BNN Provinsi Jawa Timur melalui manajemen strategi yang tepat sehingga mampu mengurangi penggunaan yang salah dari narkoba. Tujuan dari penelitian ini untuk untuk melakukan analisis lebih lanjut mengenai manajemen strategi yang dilakukan oleh BNN Provinsi Jawa Timur. Penelitian ini termasuk dalam jenis penelitian kualitatif deskriptif dengan metode pengambilan data melalui wawacara, observasi, dokumentasi, dan kajian literatur. Fokus penelitian ini menggunakan teori J. David Hunger dan Thomas L. Wheelen yang meliputi pengamatan lingkungan, perumusan strategi, implementasi startegi dan evaluasi serta pengendalian dengan menggunakan snowball sampling. Sedangkan Teknik analisis data dilakukan melalui empat tahap yaitu mengumpulkan data terkait, reduksi data yang diperoleh, penyajian data setelah diolah dan penarikan kesimpulan guna mengetahui hasil yang diharapkan. Hasil penelitian menunjukan bahwa BNN Provinsi Jawa Timur melakukan pengamatan lingkungan dengan mengidentifikasi faktor internal dan faktor eksternal organisasi, perumusan strategi dilakukan menentukan visi, misi, strategi dan kebijakan organisasi, kemudian pada tahap implementasi strategi BNN Provinsi Jawa Timur melaksanakan empat program yang meliputi program penyelenggaraan advokasi, program pemberdayaan alternatif, program pemberdayaan masyarakat serta program pengelolaan informasi dan edukasi yang dilaksanakan dengan baik serta memberikan dampak positif dalam upaya pencegahan penyalahgunaan narkoba dengan melakukan evaluasi pada tahap terakhir guna mengetahui berbagai hambatan dan kendala yang dihadapi.